A generating function approach to the enumeration of matrices in classical groups over finite fields - Fulman, Jason, 1971- (Memoirs of the American Mathematical Society, 2005)
Introduction, tables, and preliminaries Separable and cyclic matrices in classical groups Semisimple and regular matrices in classical groups Bibliography.